Mammalian U87 Small Nucleolar RNA and Its Host Gene - Makarova, J. A.; Kramerov, D. A. (Molecular biology (New York), 2005)
Most small nucleolar RNAs (snoRNAs) of the C/D box family determine the site of ribose methylation in rRNA. A new snoRNA, U87, was found in mammals, assigned to the C/D box family, and assumed to play a role in ribose methylation at G3468 of the 28S rRNA. The U87 host gene (U87HG), with an intron coding for the U87 snoRNA, was described for rodents and humans. Transcription of the human gene starts from three adjacent nucleotides, while the rat gene harbors multiple transcription start sites. The U87HG RNA resembles mRNA in some features (splicing, polyadenylation, and cytoplasmic localization) but lacks an extended open reading frame and shows a considerably lower level of conservation as compared with mRNAs of most other snoRNA host genes. The low conservation of the mRNA-like transcript of U87HG is discussed in terms of the functional significance of its exons.[PUBLICATION ABSTRACT]